Constructing Teacher Identity: Teachers Emotion in Teaching English for Pre-School Students - Wardhani, Anastasia Camelia; Ena, Ouda Teda; Mbato, Concilianus Laos (Language Circle: Journal of Language and Literature, 2021)
This research discusses how teachersÃ¢â‚¬â„¢ emotion regulation helps them construct their professional identity. To be specific, the emotion regulation studied is around teaching pre-school students. The emotion regulation investigated covers the teachersÃ¢â‚¬â„¢ behavior in the classroom setting when they are dealing with little children. The research question of this study is Ã¢â‚¬Å“How teachersÃ¢â‚¬â„¢ identity is constructed especially in teaching pre-school students?Ã¢â‚¬Â.Ã‚Â  Theories related to emotion competence, emotion regulation, and teacher identity were also reviewed in this paper. In conducting the research, teachers from one of English courses in Yogyakarta becomes the participant. The researcher uses the Critical Incident Technique (CIT). Many factors such as teaching goals, commitment, particular meaningful experiences become the main consideration in formulating the questions asked in the interview section. Actions such as the distribution of questionnaires and interviews are conducted in order to collect the data. In analyzing the data, the researcher presents the findings narratively based on the result of the questionnaire and the interview.